2020
DOI: 10.1111/os.12607
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of Preoperative Rehabilitation in Patients of Anterior Cruciate Ligament Injury

Abstract: Objectives: To investigate the biomechanical characteristics of patients with anterior cruciate ligament (ACL) injury by gait analysis, surface electromyography (SEMG), and proprioception test, and provide rehabilitation suggestions according to the results.Methods: In this retrospective cohort study, 90 adults with unilateral ACL injury, ranging in age from 19 to 45 years (66 men and 24 women, average age: 30.03 AE 7.91) were recruited for this study form May 2018 to July 2019. They were divided into three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although several studies have demonstrated better proprioception on the healthy side than on the affected side after ACL injury or reconstruction, it has also been shown that ACL injury not only decreases proprioception on the affected side, but also affects proprioception on the healthy side. Li et al similarly found that the unaffected side would decline with the decrease of proprioception on the affected side one year after ACL injury [30]. Other studies have shown that ACL injury not only leads to unilateral proprioception loss, but also to contralateral knee joint proprioception loss [31][32].…”
Section: Discussionmentioning
confidence: 97%
“…Although several studies have demonstrated better proprioception on the healthy side than on the affected side after ACL injury or reconstruction, it has also been shown that ACL injury not only decreases proprioception on the affected side, but also affects proprioception on the healthy side. Li et al similarly found that the unaffected side would decline with the decrease of proprioception on the affected side one year after ACL injury [30]. Other studies have shown that ACL injury not only leads to unilateral proprioception loss, but also to contralateral knee joint proprioception loss [31][32].…”
Section: Discussionmentioning
confidence: 97%
“…Muscle atrophy appears to occur regardless of the type of graft used to reconstruct the ACL and often occurs bilaterally ( Papannagari et al, 2006 ). The pattern of muscle strength decline is not the same for different muscles, Li et al showed that Among the VL, VM, and RF, the recovery rate of VL is the slowest ( Li et al, 2020 ). Kim et al also found significant differences in the recovery rates of extensor muscles and flexor muscles of knee ( Kim et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, when walking quickly, the patient was required to walk for 5 min at the fastest speed and the analysis test process was carried out for 3 min in the middle. The patient laid supine on the bed, baseline SEMG signals were measured during a state of muscle relaxation, then raised the leg 30° or 60° and dorsiflexed of the ankle, and maintained this position for 10 s ( Li et al, 2020 ; Mitchell et al, 2022 ; Molina-Cárdenas et al, 2022 ). The experiment was repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…We appreciate that Li et al 1 have provided us with a clinically meaningful study. We would welcome comments by the authors as this would help to further support the findings of this important study.…”
mentioning
confidence: 99%
“…Dear Editor, I n a recent issue of Orthopaedic Surgery, Li W and his colleagues published an article entitled "Biomechanical Evaluation of Preoperative Rehabilitation in Patients of Anterior Cruciate Ligament (ACL) Injury" 1 , which we read with great interest. We congratulate the authors for their efforts.…”
mentioning
confidence: 99%